APAKAH PENGETAHUAN DAN SIKAP IBU MENENTUKAN KEBERHASILAN TOILET TRAINING PADA ANAK USIA? - Ranita, Adia; Makmuriana, Lestari; Pratama, Kharisma (Jurnal Riset Keperawatan dan Kesehatan, 2024)
Background: Toilet training should be introduced early to instill good hygiene habits in children. Failure in toilet training can lead to negative parental behavior, such as harsh treatment or inappropriate discipline, potentially disrupting the child’s personality and fostering introversion. Improper toilet training can also result in long-term behavioral and psychological issues, including dependency, low self-control, and emotional distress related to defecation and urination. Objective: This study aimed to determine the relationship between mothers’ knowledge and attitudes with the success of toilet training among toddlers in Parit Baru Village. Methods: This research used a quantitative descriptive design with a cross-sectional approach. The sampling technique was purposive sampling, involving 71 respondents. Data were collected using a questionnaire and analyzed using the Kendall Tau statistical test. Results: The findings showed that most mothers had a sufficient level of knowledge, totaling 41 respondents (57.7%), and a sufficient attitude toward toilet training, totaling 43 respondents (60.6%). The statistical analysis revealed no significant relationship between mothers’ knowledge and the success of toilet training. However, a significant relationship was found between mothers’ attitudes and the success of toilet training among toddlers in Parit Baru Village. Conclusion: The success of toilet training in toddlers is not influenced by the level of maternal knowledge but is significantly associated with the mother’s attitude. Positive maternal attitudes toward consistency, patience, and encouragement play a crucial role in achieving successful toilet training outcomes